Influence of hydrogen and halogen adsorption on the photocatalytic water splitting activity of C2N monolayer: A first-principles study. (January 2019) - Ashwin Kishore, M.R.; Sjåstad, Anja Olafsen; Ravindran, P.
Abstract: Adsorption of impurity atoms or molecules on the surface of photocatalysts may improve or worsen the photocatalytic activity due to chemical bond relaxations. Herein, we demonstrate the influence of molecular adsorbates such as H2, F2, Cl2, Br2, and I2 on the electronic properties and photocatalytic activity of the nitrogenated holey graphene (C2 N) using hybrid density functional calculations including van der Waals interaction. Hydrogen and halogen molecules prefer to physisorb on the holey site except F2 which has substantial chemisorption. The halogens tend to draw electrons from C2 N monolayer due to their high electronegativity and thereby introduce new band states which significantly alters the opto-electronic and photocatalytic properties. Although F2 and Br2 adsorbed C2 N have favorable band edge positions, I2 adsorbed C2 N is more promising for hydrogen production because of its appropriate band edge positions relative to the water redox potentials. Optical absorption spectra reveals that all these systems are visible light active and therefore they could harvest more incoming light. We have demonstrated here for the first time that intermediate bandgap states can be introduced in C2 N system by adsorbing halogen molecules and our theoretical findings suggest that I2 adsorbed C2 N monolayer is a promising candidate for photocatalytic water splitting. Graphical abstract: Image 1